Association of neighborhood deprivation and hypertension: a systematic review and meta-analysis - Prakasini Satapathy (8677284) (2024)
Background Hypertension impacts nearly one billion individuals and is a primary health challenge. While traditional perspectives have focused on individual behavior and genetics as principal risk factors, recent research underscores the profound influence of socioeconomic factors within neighborhoods on the risk of hypertension. This systematic review and meta-analysis is aimed to elucidate the association between neighborhood deprivation and the risk of hypertension. Methods A comprehensive literature search was conducted across PubMed, Embase, and Web of Science from inception until December 25, 2023. Observational studies defining neighborhood deprivation and reporting hypertension incidence were included. Nested Knowledge software was used for screening and data extraction, with study quality assessed using the Newcastle-Ottawa Scale. Statistical analysis was performed with R software (V 4.3), using a random-effects model to calculate the pooled relative risk (RR). Results Twenty-six studies were included in the qualitative analysis and 22 in the meta-analysis, covering over 62 million participants. The pooled RR was 1.139 (95% CI: 1.006 – 1.290), p=0.04, indicating a higher hypertension risk in deprived neighborhoods. Subgroup analyses showed variability by country and deprivation assessment methods. RR varied from 1.00 in Japan (95% CI: 0.93–1.08) to 1.60 (95% CI: 1.07–2.39) in France and 1.57 (95% CI: 0.67–3.70) in Germany, with significant heterogeneity observed in measures of neighborhood deprivation. Conclusion Our analysis confirms a significant association between neighborhood deprivation and hypertension, underscoring the importance of socioeconomic factors in public health. It highlights the need for targeted local assessments and interventions. Future research should explore the causal mechanisms and effectiveness of interventions addressing neighborhood deprivation. Other Information Published in: Current Problems in Cardiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cpcardiol.2024.102438